ANALSIS TENTANG PENERAPAN AKAD IJARAH DAN PENYEBAB GAGAL BAYAR (DEFAULT) SUKUK IJARAH - Lestari, Lutfi Bangun (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2022)
This study aims to analyze the causes of default on sukuk ijarah at PT. X and the suitability of the application of sharia principles in the implementation of the issuance of sukuk ijarah at PT. X. This type of research is a qualitative research. Using secondary data, obtained from the Indonesia Stock Exchange website, PT.X financial reports, journals, news and so on. This study uses descriptive analysis, which describes the analysis of the causes of PT.X's sukuk default. The result of this research is that it can be said that the implementation of the ijarah tribe of PT. X is in accordance with Islamic principles. As for the causes of default, namely, the use of funds from sukuk ijarah to pay debts, a decrease in company cash which has an impact on the decline in the rating of sukuk, this has an impact on the decline in share value as well, the company's income is reduced, so there is a default, entangled in legal cases from several children companies that caused a lack of cash supply to the parent company and had to lose some assets because they had to be sold.